2015
DOI: 10.19173/irrodl.v16i4.2124
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Roles of Social Participation in Mobile Social Media Learning: A Social Network Analysis

Abstract: <p class="BODYTEXT">Social media is increasingly becoming an essential platform for social connectivity in our daily lives. The availability of mobile technology has further fueled its importance – making it a ubiquitous tool for social interaction. An emerging mode of learning is the mobile social media learning where social media is used in the mobile learning mode. However, limited studies have been conducted to investigate roles of social participation in this field. Thus, the study investigates role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 37 publications
(52 reference statements)
2
38
0
Order By: Relevance
“…In the studies on these applications, generally, minimisation of the problems and use of their potential to support education processes are emphasized. Also, in this research, it was mentioned that they provide unstructured learning environment and can be used as effective tools in education (Cain & Policastri, 2011;Lampe, Wohn, Vitak, Ellison, and Wash 2011;Madge, Meek, Wellens, and Hooley, 2009;Towner & Munoz, 2011;Arteaga Sánchez et al, 2014;Norman, Nordin, Din, Ally, and Dogan, 2015). Yet, it is early to know what impact the WhatsApp application, which has an important place in the daily lives of youg people and has the qualities to be recognised as social network, will have on education.…”
Section: Resultsmentioning
confidence: 89%
“…In the studies on these applications, generally, minimisation of the problems and use of their potential to support education processes are emphasized. Also, in this research, it was mentioned that they provide unstructured learning environment and can be used as effective tools in education (Cain & Policastri, 2011;Lampe, Wohn, Vitak, Ellison, and Wash 2011;Madge, Meek, Wellens, and Hooley, 2009;Towner & Munoz, 2011;Arteaga Sánchez et al, 2014;Norman, Nordin, Din, Ally, and Dogan, 2015). Yet, it is early to know what impact the WhatsApp application, which has an important place in the daily lives of youg people and has the qualities to be recognised as social network, will have on education.…”
Section: Resultsmentioning
confidence: 89%
“…In this review, we examined the progress and trends of the past decade that could offer directions for future research. The authors hope this review offers greater insights into the cooperative language learning and encourages further research on STAD among ESL learners in enhancing speaking performance with effective instructional design (Adnan & Ritzhaupt, 2018;Adnan, 2018) and alternative assessment such as usage of learning analytics and network diagrams (Norman, Nordin, Din, Ally, & Dogan, 2015;Norman, Nordin, Yunus, & Ally,…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a number of studies have shown that they provide unstructured learning environment for learners and could be used effectively in learning (Cain & Policastri, 2011;Lampe, Wohn, Vitak, Ellison, & Wash, 2011;Madge et al, 2009;Norman, Nordin, Din, Ally, & Dogan, 2015;Sánchez et al, 2014). These studies all reveal their potential to affect the forms of communication of the individuals and the development of the language during the process of education besides everyday life.…”
mentioning
confidence: 99%